Employee performance in Bappeda Palembang as perceived through interpersonal communication and work environment - Yasir Arafat; Tri Darmawati; Harridlil Mukminin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2021)
The purpose of this study was to determine the effect of interpersonal communication and the work environment on employee performance in Bappeda Palembang. The sample was 40 employees in Bappeda  Palembang. The survey for this study is based on 40 workers as respondents. Data were gathered and organized into a list of questions. The spss for Windows version 22 was used to analyze the outcomes using simple linear regression analysis, multiple linear regression analyses, t-tests, and f-tests. The interpersonal communication has a partially negative and insignificant effect on employee performance, work environment has a positive and significant effect on employee performance. Furthermore, obtained interpersonal communication as well as the workplace environment have a significant impact on employee performance.